209. Impact of a Risk-based CAP Prescribing Guideline Paired with Antimicrobial Stewardship to Improve Antibiotic Prescribing for Patients at Low Risk for Drug-Resistant Pathogens. (26th November 2018) - Cruce, Caroline; Postelnick, Michael; Martin, David; Sutton, Sarah; Wunderink, Richard G; Zembower, Teresa; Scheetz, Marc H; Rhodes, Nathaniel J
Abstract: Background: Antimicrobial stewardship programs (ASPs) reduce the burden of multidrug-resistant organisms and improve antibiotic prescribing. Concerns about drug-resistant pathogens (DRPs) in community-acquired pneumonia (CAP) lead to over-prescribing of broad-spectrum antibiotics, and ASP interventions to improve CAP prescribing are not well defined. In 2017, our hospital implemented a CAP guideline for patients at low risk for DRPs along with ASP support. The purpose of this study was to evaluate the impact of the guideline with ASP support on CAP-specific antibiotic prescribing. Methods: This was a pragmatic two-phase quasi-experimental analysis of CAP-specific antibiotic consumption before and after implementation of a CAP guideline evaluated according to each phase of implementation. The guideline provided Gram-positive and Gram-negative risk factors and guidance on oral fluoroquinolone (FQs) alternatives. ASP interventions were implemented in two phases: (A) prospective audit and feedback in July 2016 and (B) publication of guideline with education in March 2017. Impact of each intervention was evaluated by interrupted time series segmented-regression analysis. Univariate statistics were calculated using EpiInfo 7. Least-squares segmented regressions were completed in Microsoft Excel. Results: CAP-specific antibiotic administrations were 782 over the entire study period, with 764, 771, and 928 administrations observed before phase A, after A, and after B, respectively. Macrolide consumption increased after the guideline ( P = 0.029). We observed a significant step change decrease in FQ consumption was observed after phase A) ( P = 0.039) and a positive upward trend in oral alternatives agents after phase B ( P = 0.090), as shown in the figure. Consumption of broad Gram-negative agents and vancomycin/linezolid were not significantly different after the guideline. Conclusion: Implementation of a CAP guideline with patient-specific and DRP risk factors was associated with significant changes in CAP-specific prescribing. Changes in prescribing were temporally associated with ASP interventions. Additional studies into the impact of this guideline on correct classification of Gram-negative resistance and clinical outcomes are needed. Disclosures: D. Martin, GlaxoSmithKline: Independent Contractor, Salary Syneos Health: Employee, Salary. R. G. Wunderink, Achaogen: Consultant, Consulting fee. Arsanis: Consultant, Consulting fee. Bayer: Consultant, Consulting fee. GlaxoSmithKline: Consultant, Consulting fee. KBP Biosciences: Consultant, Consulting fee. Meiji-Seiko: Consultant, Consulting fee. Merck: Consultant, Consulting fee. Nabriva: Consultant, Consulting fee. Polyphor: Consultant, Consulting fee. Roche/Genetech: Consultant, Consulting fee. Shionogi: Consultant, Consulting fee. The Medicines Company: Consultant, Consulting fee. Accelerate Diagnostics: Consultant, Consulting fee. Curetis: Consultant, Consulting fee. bioMerieux: Consultant, Consulting fee. M. H. Scheetz, Merck & Co., Inc.: Grant Investigator, Grant recipient. Bayer: Consultant, Consulting fee.